Porous alumina as well as preparation method and application thereof

By coating porous alumina with a moderate specific surface area on the lithium battery separator, the problem of insufficient absorption of electrolyte by the separator is solved, the liquid absorption rate and cycle life of the battery are improved, and the demand for lightweight is met.

CN119349611APending Publication Date: 2025-01-24SUZHOU GINET NEW MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411525866.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing lithium battery separators lead to electrolyte consumption, increased impedance, battery capacity and power attenuation during circulation, and under the demand for lightweight development, the separators lack the absorption of electrolyte.

Method used

The coated aluminum aluminum is used to form a pore structure through a specific preparation method to improve the absorption of the electrolytes of the aluminum oxide powder and paint it on the surface of the diaphragm.

Benefits of technology

It improves the fluid rate, fluid amount and liquid ability of the diaphragm, meets the demand of light weight and absorbing more electrolytes, extend the cycle life of the battery and improves electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349611A_ABST
    Figure CN119349611A_ABST
Patent Text Reader

Abstract

The invention discloses porous aluminum oxide as well as a preparation method and application thereof, and belongs to the technical field of battery materials. The porous alumina has a pore structure, the specific surface area of the porous alumina is 10m < 2 > / g-50m < 2 > / g, and the apparent density of the porous alumina is 2g / cm < 3 >-3g / cm < 3 >. The porous alumina is moderate in specific surface area, and few unsaturated aluminum elements are exposed on the surface, so that less water and hydroxyl are adsorbed, and the moisture content is low; the porous alumina has relatively low apparent density, and can effectively meet the requirement of light weight; moreover, the porous aluminum oxide has a pore structure, can improve the absorption of aluminum oxide powder to electrolyte, and shows higher liquid absorption rate, liquid absorption amount and liquid retention capacity on a coated diaphragm, so that the electrolyte can be quickly and effectively transmitted and supplemented in the charging and discharging process of the battery. Therefore, the porous alumina can meet the requirements of diaphragm light weight and absorption and storage of more electrolyte, and the corresponding diaphragm can improve the electrochemical performance of the lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to porous alumina and a preparation method and application thereof. Background Art

[0002] At present, the search for high specific energy battery systems is the main research direction and the main way to achieve lightweight battery systems. Compared with the lightweight structure and process, the effect of lightweight materials is immediate. With the increase in battery capacity requirements, the reduction of diaphragm thickness in battery structures is one of the inevitable trends. In addition, porous materials also play an important role in lightweight applications due to their important advantages of light weight and low density.

[0003] The diaphragm is one of the main components of lithium batteries because its structure and performance play an important role in battery cycle life, safety performance, energy density, etc. Polyolefin diaphragms are the current mainstream diaphragms, but their inherent disadvantage is the poor thermal stability of organic matter. The most effective solution is to coat the surface of the diaphragm with high thermal stability inorganic ceramic particles to improve heat resistance and battery safety.

[0004] During the first and subsequent charge and discharge processes of lithium batteries, a solid electrolyte passivation layer, namely the SEI film, will be formed and continuously grow. SEI is an excellent conductor of lithium ions, which can effectively reduce the probability of internal short circuits, improve self-discharge, and effectively prevent the co-embedding of solvent molecules, thus avoiding the damage to the electrode material caused by the co-embedding of solvent molecules, thereby greatly improving the cycle performance and service life of the electrode. However, during the cycle, SEI continues to grow and consume electrolyte, which ultimately causes the loss of Li, increased impedance, battery capacity attenuation and power decay. In order to ensure the capacity and power of the battery, it is necessary to increase the content of the electrolyte. At the same time, due to the demand for lightweight development of batteries, it is an inevitable trend to increase the energy density of the battery, increase the content of active substances in the battery, reduce the thickness of the battery diaphragm, and reduce the thickness of the ceramic layer, which will further reduce the content of the electrolyte in the battery, which is contrary to the above. Therefore, in order to take both into account, it is necessary to increase the absorption of the electrolyte by the diaphragm while meeting the lightweight requirements of the diaphragm.

[0005] At present, there are no inorganic ceramic particles that can solve the above technical problems.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The object of the present invention is to provide a porous alumina and a preparation method and application thereof, so as to solve or improve the above-mentioned technical problems.

[0008] The present invention can be implemented like this:

[0009] In a first aspect, the present invention provides a porous alumina having a pore structure and a specific surface area of ​​10 m 2 / g~50m 2 / g, the apparent density is 2g / cm 3 ~3g / cm 3 .

[0010] In an optional embodiment, the porous alumina further has at least one of the following characteristics:

[0011] Feature 1: The pore size of porous alumina ranges from 4nm to 80nm;

[0012] Feature 2: The particle size of porous alumina ranges from 0.3 μm to 2 μm;

[0013] Feature 3: The pore volume of porous alumina is 0.004 cm 3 / g to 0.08cm 3 / g;

[0014] Feature 4: The pH value of porous alumina is 8.5 to 10;

[0015] Feature 5: The surface hydroxyl content of porous alumina is greater than 0 and ≤ 10 / nm 2 ;

[0016] Feature 6: The morphology of porous alumina is prismatic;

[0017] Feature 7: The ratio of the bulk density to the apparent density of the porous alumina is 1:9 to 2:11.

[0018] In an optional embodiment, the specific surface area of ​​the porous alumina is 12 m 2 / g~50m 2 / g.

[0019] In an optional embodiment, the apparent density of the porous alumina is 2.1 g / cm 3 ~2.9g / cm 3 .

[0020] In an optional embodiment, the pore size of the porous alumina is in the range of 4.0 nm to 28 nm.

[0021] In an optional embodiment, the median particle size of the porous alumina is 0.4 μm to 0.5 μm.

[0022] In an optional embodiment, the pore structure includes openings and / or depressions on the surface of the alumina powder, and tunnels inside the alumina powder;

[0023] The existence of the tunnel includes independent single tunnels and / or interconnected tunnels.

[0024] The hole shapes of the hole structure include circular and / or polygonal.

[0025] In an optional embodiment, each face of the porous alumina has at least one of openings, recesses, and tunnels;

[0026] When the porous alumina has tunnels, at least a portion of the tunnels extending inward from the surface of the alumina powder can be observed in an image with a transmission electron microscope scale of 10 nm to 50 nm.

[0027] In a second aspect, the present invention provides a method for preparing a porous alumina as described in any of the aforementioned embodiments, comprising the following steps: mixing aluminum hydroxide, aluminum isopropoxide, isopropanol, a nucleation promoter and water in a mass ratio of (20-40):(5-15):(5-15):(5-12):(25-58) and reacting to obtain an intermediate product Al2O3·nH2O, wherein 0.7≤n≤1.5; and calcining the intermediate product.

[0028] In an alternative embodiment, the nucleation promoter includes at least one of sodium hydroxide and citric acid.

[0029] In an optional embodiment, when the nucleation promoter includes sodium hydroxide and citric acid at the same time, the mass ratio of sodium hydroxide to citric acid is (1-10):5.

[0030] In an optional embodiment, the total volume of aluminum hydroxide, aluminum isopropoxide, isopropanol, nucleation promoter and water accounts for 20% to 70% of the volume of the reaction container.

[0031] In an optional embodiment, the reaction includes: first reacting at 40°C to 70°C for 3h to 5h, and then reacting at 120°C to 220°C for 6h to 24h.

[0032] In an optional embodiment, the heating rate during the reaction is 1°C / min to 5°C / min.

[0033] In an optional embodiment, the calcination has at least one of the following characteristics:

[0034] Feature 7: Calcination temperature is 400°C to 1100°C;

[0035] Feature 8: Calcination time is 2h to 12h;

[0036] Feature 9: The heating rate of the calcination process is 1°C / min to 5°C / min.

[0037] In a third aspect, the present invention provides a diaphragm, the surface of which is coated with the porous alumina according to any one of the aforementioned embodiments.

[0038] In an optional embodiment, the liquid absorption rate of the membrane is not less than 85%.

[0039] In a fourth aspect, the present invention provides a lithium battery having the separator of the aforementioned embodiment.

[0040] The beneficial effects of the present invention include:

[0041] The porous alumina provided by the present invention has a moderate specific surface area (10m 2 / g~50m 2 / g), less unsaturated aluminum elements are exposed on the surface, so less water and hydroxyl adsorption is achieved, and the moisture content is low; in addition, the porous alumina provided by the present invention has a lower apparent density (2g / cm 3 ~3g / cm 3 ), which can effectively meet the lightweight requirements; in addition, the porous alumina provided by the present invention has a pore structure, which can improve the absorption of electrolyte by alumina powder, and show higher liquid absorption rate, liquid absorption amount and liquid retention capacity on the coated diaphragm, so that during the charge and discharge process of the battery, the electrolyte can be quickly and effectively transported and replenished.

[0042] Therefore, the porous alumina provided by the present invention can meet the requirements of lightweight diaphragm and absorption and storage of more electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0044] Figure 1 This is a field emission scanning electron microscope result of the porous alumina prepared in Example 4;

[0045] Figure 2 This is a transmission electron microscopy result of the porous alumina prepared in Example 4;

[0046] Figure 3 for Figure 2 A partial enlarged view of

[0047] Figure 4 This is a diagram showing the corresponding liquid absorption of different diaphragms under the first condition in the test example;

[0048] Figure 5 This is a diagram showing the liquid absorption of different membranes under the second condition in the test example. DETAILED DESCRIPTION

[0049] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0050] The porous alumina provided by the present invention and its preparation method and application are described in detail below.

[0051] The present invention provides a porous alumina having a pore structure and a specific surface area of ​​the porous alumina of 10 m 2 / g~50m 2 / g, the apparent density is 2g / cm 3 ~3g / cm 3 .

[0052] It should be noted that ordinary alumina has no pore structure, small specific surface area and high density. During diaphragm coating, the electrolyte can only be stored in the gaps between the powders, and its liquid absorption and retention capabilities are low. General porous alumina, such as γ-alumina used as a catalyst, has a large specific surface area, more unsaturated aluminum atoms exposed on the surface, and a strong ability to adsorb water. It often contains a higher moisture content, which makes it difficult to dry the diaphragm after coating, which may further affect the electronic conductivity of the diaphragm.

[0053] The porous alumina provided by the present invention has a moderate specific surface area (10m 2 / g~50m 2 / g), less unsaturated aluminum elements are exposed on the surface, so less water and hydroxyl adsorption is achieved, and the moisture content is low; in addition, the porous alumina provided by the present invention has a lower apparent density (2g / cm 3 ~3g / cm 3 ), which can effectively meet the lightweight requirements; in addition, the porous alumina provided by the present invention has a pore structure, which can improve the absorption of electrolyte by alumina powder, and show higher liquid absorption rate, liquid absorption amount and liquid retention capacity on the coated diaphragm, so that during the charge and discharge process of the battery, the electrolyte can be quickly and effectively transported and replenished.

[0054] Therefore, the porous alumina provided by the present invention can meet the requirements of lightweight diaphragm and absorption and storage of more electrolyte.

[0055] In some optional embodiments, the specific surface area of ​​the porous alumina can be 10 m 2 / g, 15m 2 / g, 20m 2 / g, 25m 2 / g, 30m 2 / g, 35m2 / g, 40m 2 / g, 45m 2 / g or 50m 2 / g, etc., can also be 10m 2 / g~50m 2 In some exemplary embodiments, the specific surface area of ​​the porous alumina can be 12 m 2 / g~50m 2 / g, such as 12.8582m 2 / g, 21.2312m 2 / g, 21.9345m 2 / g, 22.8534m 2 / g, 23.1247m 2 / g, 30.8867m 2 / g, 42.2781m 2 / g or 48.3547m 2 / g, etc.

[0056] In some optional embodiments, the apparent density of the porous alumina may be 2 g / cm 3 , 2.5g / cm 3 or 3g / cm 3 etc., can also be 2g / cm 3 ~3g / cm 3 In some exemplary embodiments, the apparent density of the porous alumina may be 2.1 g / cm 3 ~2.9g / cm 3 , such as 2.1277g / cm 3 , 2.3159g / cm 3 , 2.2413g / cm 3 , 2.26693g / cm 3 , 2.2833g / cm 3 , 2.3095g / cm 3 , 2.4841g / cm 3 or 2.8615 g / cm 3 wait.

[0057] The density of conventional alumina is 3.9g / cm 3 ~4.0g / cm 3 The apparent density of existing crystalline granular porous alumina is usually 3.2 g / cm 3The density of the porous alumina with a high specific surface area formed by gel calcination is not much reduced. However, the density of the porous alumina with a high specific surface area formed by gel calcination is more significantly reduced, but due to its high specific surface area, it is difficult to remove moisture and is easy to combine with water, so it is not suitable for batteries but more suitable for catalysts. The porous alumina provided by the present invention breaks the above conventional settings and proposes a porous alumina with a lower density and a larger specific surface area.

[0058] In some optional embodiments, the ratio of the bulk density to the apparent density of the porous alumina may be 1:9 to 2:11, such as 1:9, 1.5:10 or 2:11, or other values ​​within the range of 1:9 to 2:11. In some exemplary embodiments, the ratio of the bulk density to the apparent density of the porous alumina may be 0.14 to 0.18, such as 0.140, 0.143, 0.152, 0.153, 0.154, 0.157, 0.164 or 0.172, etc.

[0059] It should be noted that "bulk density" is different from "apparent density", where "apparent density" refers to the mass per unit volume of the material in its natural state; the volume in its natural state refers to the volume of the material including pores. In the present invention, apparent density can be understood as the density under the assumption that alumina is non-porous, and the density difference between it and dense alumina can reflect the pore content of porous alumina. "Bulk density" refers to the mass per unit volume of loose particulate material (powder, granular or fibrous, etc.) in its natural stacking state; the volume under bulk density refers to the sum of the volumes of the solid part, pore part and void part of the material. When measuring, it refers to the volume of the container used, and mass refers to the mass of the material filled in the container for measurement.

[0060] In some optional embodiments, the pore volume of the porous alumina may be 0.004 cm 3 / g to 0.08cm 3 / g, such as 0.004cm 3 / g, 0.01cm 3 / g, 0.015cm 3 / g, 0.02cm 3 / g, 0.025cm 3 / g, 0.03cm 3 / g, 0.035cm 3 / g, 0.04cm 3 / g, 0.045cm 3 / g, 0.05cm 3 / g, 0.055cm 3 / g, 0.06cm 3 / g, 0.065cm 3 / g, 0.07cm3 / g, 0.075cm 3 / g or 0.08cm 3 / g, etc., can also be 0.004cm 3 / g to 0.08cm 3 In some exemplary embodiments, the pore volume of the porous alumina may be 0.030 cm 3 / g~0.071cm 3 / g, such as 0.031cm 3 / g, 0.040cm 3 / g, 0.041cm 3 / g, 0.055cm 3 / g, 0.062cm 3 / g, 0.069cm 3 / g or 0.071cm 3 / g, etc.

[0061] In some optional embodiments, the pore size of the porous alumina can range from 4 nm to 80 nm. In other words, the pore size of the porous alumina can be 4 nm, 8 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 65 nm, 70 nm, 75 nm or 80 nm, etc., or other values ​​within the range of 4 nm to 80 nm. In some exemplary embodiments, the pore size of the porous alumina can range from 4.0 nm to 28 nm, such as 4.132 nm, 4.314 nm, 6.824 nm, 8.377 nm, 10.032 nm, 10.215 nm, 10.337 nm or 27.924 nm, etc.

[0062] In some optional embodiments, the particle size range of the porous alumina can be 0.3μm to 2μm. In other words, the particle size of the porous alumina can be 0.3μm, 0.5μm, 0.8μm, 1.0μm, 1.2μm, 1.5μm, 1.8μm or 2.0μm, etc., or other values ​​within the range of 0.3μm to 2μm.

[0063] In some optional embodiments, the median particle size of the porous alumina may be 0.4 μm to 0.5 μm, such as 0.4 μm, 0.42 μm, 0.45 μm, 0.48 μm or 0.5 μm, etc., or other values ​​within the range of 0.4 μm to 0.5 μm.

[0064] In some optional embodiments, the pH value of the porous alumina may be 8.5-10, such as 8.5, 9.0, 9.5 or 10, or other values ​​within the range of 8.5-10.

[0065] In some optional embodiments, the surface hydroxyl content of the porous alumina is greater than 0 and less than 10 / nm 2 , such as 10 / nm 2 , 9 / nm 2 , 8 / nm 2 , 7 / nm 2 , 6 / nm 2 , 5 / nm 2 , 4 / nm 2 , 3 / nm 2 , 2 / nm 2 or 1 / nm 2 etc., and can also be >0 and ≤10 / nm 2 Other values ​​within the range.

[0066] Normally, activated alumina is acidic because it has a large specific surface area and many unsaturated aluminum ions on the surface, which can adsorb hydroxyl groups to ionize hydrogen ions; while general metal oxides tend to release hydroxide ions in water. The porous alumina provided by the present invention has low surface hydroxyl content and low water content.

[0067] In some optional embodiments, the porous alumina has a prismatic shape. The porous alumina with this shape can increase the gap between the alumina particles. The prismatic alumina particles have multiple contact forms such as co-point, co-line, co-plane, and point-plane during the stacking process. Compared with ordinary alumina (spherical), it is not easy to form a dense stacking form, thereby increasing the gap between the particles. This has certain benefits for the battery separator after coating, including reducing air permeability, reducing surface density, and increasing the infiltration rate of the electrolyte; at the same time, such angular particles can also reduce the thermal shrinkage of the separator after stacking.

[0068] It should be emphasized that the inventors found that the density of porous alumina and the pH value of its slurry are not only related to the pore size and pore distribution in the porous alumina, but also to the crystal system, morphology, etc. of the porous alumina. This may be because in the preparation process of porous alumina, by controlling the morphology of its precursor and the content of crystal water therein, and then controlling its heating rate and insulation process during the sintering process, the overflow rate of water molecules and the lattice rearrangement of aluminum oxygen atoms are controlled, so that it forms an aluminum oxygen atom lattice of a specific structure on the basis of maintaining its morphology, so that the pores in the porous alumina gradually merge, and its apparent density decreases instead. At the same time, in the aluminum oxygen atom lattice, aluminum atoms are less exposed or less distributed on the surface of the grains, so that it is not easy to combine with the hydroxyl groups in the slurry, so that the slurry is alkaline, reducing the possibility of aluminum oxide consuming electrolyte, and improving its dispersibility and stability. In particular, during the rearrangement of aluminum and oxygen atoms, the pores in alumina are mainly fused in a specific direction to form directional through-holes, which are beneficial for shortening the conduction path of lithium ions, improving the conduction efficiency of lithium ions, and improving the conductivity of particles.

[0069] As mentioned above, the porous alumina provided by the present invention has a significantly lower density and a smaller specific surface area than conventional alumina, has a weaker bonding force with hydroxyl groups in the slurry, and has an orthorhombic system with large crystal particles. The porous alumina not only has good dispersibility, thermal shrinkage, and strength, but also has a low density and low consumption of electrolyte, which makes the gas production of the battery based on the alumina particularly small, and has good bonding force with the diaphragm substrate and is not easy to damage the diaphragm substrate and other excellent properties.

[0070] In some optional embodiments, the pore structure includes openings and / or depressions on the surface of the alumina powder, and tunnels inside the alumina powder, wherein the tunnels exist in the form of independent single tunnels and / or interconnected tunnels.

[0071] In some cases, the pore structure located on the surface of the alumina powder may be only in the form of openings; in some cases, the pore structure located on the surface of the alumina powder may be only in the form of depressions; in some cases, the pore structure located on the surface of the alumina powder may contain both open and depressions.

[0072] In some cases, the tunnels inside the alumina powder are all independent, that is, they do not cross or communicate with each other, for example, they can be parallel; in some cases, the tunnels inside the alumina powder are all interconnected; in some cases, the tunnels inside the alumina powder include both independent tunnels and tunnels that communicate with each other.

[0073] In some preferred embodiments, each surface of the porous alumina has at least one of openings, recesses and tunnels.

[0074] In some cases, all faces of the porous alumina may have only openings; in some cases, all faces of the porous alumina may have only depressions; in some cases, all faces of the porous alumina may have only tunnels; in some cases, some faces of the porous alumina have only openings or depressions or tunnels, and the remaining faces have at least two of openings, depressions and tunnels; in some cases, all faces of the porous alumina contain openings, depressions and tunnels at the same time.

[0075] When the porous alumina has tunnels, at least a portion of the tunnels extending inward from the surface of the alumina powder can be observed in an image with a transmission electron microscope scale of 10 nm to 50 nm.

[0076] In some optional embodiments, the hole shape of the hole structure includes circular and / or polygonal shapes.

[0077] In some cases, the pore shapes of the pore structure are all quasi-circular; in some cases, the pore shapes of the pore structure are all polygonal; in some cases, the pore shapes of the pore structure include both quasi-circular and polygonal.

[0078] In the present invention, the pore content of porous alumina, especially the open pores, through pores and pore sizes, directly affects the powder's absorption of the electrolyte. The porous alumina having the above-mentioned pore characteristics of the present invention can exhibit excellent liquid absorption rate, liquid absorption amount and liquid retention capacity on the coated diaphragm, and can quickly and effectively transport and replenish the electrolyte during the battery's charge and discharge process.

[0079] As mentioned above, the porous alumina provided by the present invention can meet the requirements of lightweight diaphragm and absorb and store more electrolyte.

[0080] Correspondingly, the present invention also provides a method for preparing the above-mentioned porous alumina, which may include the following steps: mixing aluminum hydroxide, aluminum isopropoxide, isopropanol, a nucleation promoter and water in a mass ratio of (20-40):(5-15):(5-15):(5-12):(25-58) and reacting to obtain an intermediate product Al2O3·nH2O, wherein 0.7≤n≤1.5; and calcining the intermediate product.

[0081] The reaction principle includes: the hydrolysis of aluminum isopropoxide will form aluminum hydroxide sol with a smaller particle size, which serves as a seed in the reaction process, and isopropanol can be used to inhibit aluminum isopropoxide to ensure that the seed has a suitable size. Furthermore, the seed serves as a nucleation matrix, and aluminum hydroxide serves as a reactant. As the reaction proceeds, aluminum hydroxide gradually grows on the seed until it grows to an intermediate product with a desired particle size; the intermediate product is then calcined to obtain porous alumina.

[0082] In some optional embodiments, the nucleation promoter may illustratively but not limitatively include at least one of sodium hydroxide and citric acid. When the nucleation promoter includes both sodium hydroxide and citric acid, the mass ratio of sodium hydroxide to citric acid may be (1-10):5, such as 1:5, 2:5, 5:5, 8:5 or 10:5, or other values ​​within the range of (1-10):5.

[0083] In some optional embodiments, the total volume of aluminum hydroxide, aluminum isopropoxide, isopropanol, nucleation promoter and water can account for 20% to 70% of the volume of the reaction container, such as 20%, 30%, 40%, 50%, 60% or 70%, etc., or other values ​​within the range of 20% to 70%. The proportion of the total volume of aluminum hydroxide, aluminum isopropoxide, isopropanol, nucleation promoter and water in the reaction container will affect the pressure, the nucleation rate of the overall reaction, the size of the grains, etc.

[0084] In some optional embodiments, the reaction includes: first reacting at 40°C to 70°C for 3h to 5h, and then reacting at 120°C to 220°C for 6h to 24h.

[0085] The reaction is carried out at 40°C to 70°C for 3h to 5h to achieve the hydrolysis of aluminum isopropoxide. The temperature of the reaction process can be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C, or other values ​​within the range of 40°C to 70°C. The reaction time can be 3h, 3.5h, 4h, 4.5h or 5h, or other values ​​within the range of 3h to 5h.

[0086] The reaction is carried out at 120°C to 220°C for 6h to 24h to achieve the gradual growth of aluminum hydroxide on the seed crystal. The temperature of the reaction process can be 120°C, 140°C, 160°C, 180°C, 200°C or 220°C, etc., or other values ​​within the range of 120°C to 220°C. The reaction time can be 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h or 24h, etc., or other values ​​within the range of 6h to 24h.

[0087] The heating rate in the above reaction process can be 1°C / min to 5°C / min, such as 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min, or other values ​​within the range of 1°C / min to 5°C / min.

[0088] In some optional embodiments, the calcination temperature can be 400°C to 1100°C, such as 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C or 1100°C, or other values ​​within the range of 400°C to 1100°C.

[0089] The calcination time may be 2 h to 12 h, such as 2 h, 4 h, 6 h, 8 h, 10 h or 12 h, etc., or other values ​​within the range of 2 h to 12 h.

[0090] The heating rate of the calcination process can be 1°C / min to 5°C / min, such as 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min, or other values ​​within the range of 1°C / min to 5°C / min.

[0091] The above reaction process can also be carried out under stirring conditions.

[0092] It should be noted that extending the holding time will cause the crystal form to transform to a high-temperature phase, that is, the low-temperature phase will decrease and the high-temperature phase will increase.

[0093] It should also be noted that different pore characteristics will be presented by adjusting the calcination conditions according to the different crystalline water content of the intermediate product. The calcination temperature affects the pore volume, pore size and specific surface area of ​​alumina. Under low calcination temperature conditions, the pores are small and densely distributed; with the increase of calcination temperature, the escape of crystalline water and the lattice rearrangement of aluminum oxygen atoms, the pore size gradually increases, and the pores will become interconnected. The escape of water molecules and the formation of pores reduce the overall quality; the gaps left by the escape of water will be filled and will not collapse due to the diffusion of aluminum oxygen atoms. As the lattice expands and contracts, the intermediate undergoes a phase transition and pores are formed, while the overall volume change remains small, which ultimately manifests itself as a lower apparent density than solid alumina, which is conducive to achieving the lightweight requirements of batteries.

[0094] Among them, the vacancies left by the removal of crystal water and the lattice rearrangement formed by the movement of aluminum ions jointly form holes of different ranges. These holes can be open or closed, or continuous channels formed inside, resulting in a reduction in the overall apparent density of alumina, which is conducive to lightweighting. Moreover, the pore structure, especially the continuous channels that run through the entire crystal, can absorb electrolyte faster under capillary action; and the porous structure also allows the powder to absorb and store electrolyte by itself in addition to relying on the gaps between the separate bodies to store electrolyte, thereby increasing the overall liquid absorption of the diaphragm.

[0095] In addition, the present invention also provides a diaphragm, the surface of which is coated with the porous aluminum oxide.

[0096] In some optional embodiments, the liquid absorption rate of the membrane is not less than 85%.

[0097] The separator can improve the heat resistance and safety of the battery.

[0098] Furthermore, the present invention also provides a lithium battery having the above-mentioned separator.

[0099] The lithium battery is not only light in weight but also has a high capacity and good electrochemical performance.

[0100] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0101] Example 1

[0102] This embodiment provides a porous aluminum oxide, and the preparation method thereof includes:

[0103] S1: Aluminum hydroxide, aluminum isopropoxide, isopropanol, sodium hydroxide, citric acid and water are put into a hydrothermal reactor in a mass ratio of 25:15:15:8:4:33 (the total volume of aluminum hydroxide, aluminum isopropoxide, isopropanol, sodium hydroxide, citric acid and water accounts for 45% of the hydrothermal reactor), the temperature is increased to 60°C at a heating rate of 5°C / min, the reaction is carried out at a stirring speed of 20 Hz for 4 hours, and then the temperature is increased to 170°C at a heating rate of 5°C / min for 15 hours to obtain an intermediate product Al2O3·nH2O, where n is 1.0.

[0104] S2: After washing, filtering, demagnetizing and drying the intermediate product, the temperature is increased to 600° C. at a heating rate of 3° C. / min and calcined for 7 h to obtain porous alumina.

[0105] Example 2

[0106] The difference between this embodiment and embodiment 1 is that the calcination temperature is 750°C.

[0107] Example 3

[0108] The difference between this embodiment and embodiment 1 is that the calcination temperature is 900°C.

[0109] Example 4

[0110] The difference between this embodiment and embodiment 1 is that the calcination temperature is 1000°C.

[0111] Example 5

[0112] This embodiment provides a porous aluminum oxide, and the preparation method thereof includes:

[0113] S1: Aluminum hydroxide, aluminum isopropoxide, isopropanol, sodium hydroxide, citric acid and water are put into a hydrothermal reactor in a mass ratio of 20:15:15:6:3:41 (the total volume of aluminum hydroxide, aluminum isopropoxide, isopropanol, sodium hydroxide, citric acid and water accounts for 20% of the hydrothermal reactor), the temperature is increased to 40°C at a heating rate of 1°C / min, the reaction is carried out at a stirring speed of 20 Hz for 5 hours, and then the temperature is increased to 120°C at a heating rate of 1°C / min for 24 hours to obtain an intermediate product Al2O3·nH2O, where n is 1.5.

[0114] S2: After washing, filtering, demagnetizing and drying the intermediate product, the temperature is increased to 400° C. at a heating rate of 1° C. / min and calcined for 12 h to obtain porous alumina.

[0115] Example 6

[0116] This embodiment provides a porous aluminum oxide, and the preparation method thereof includes:

[0117] S1: Aluminum hydroxide, aluminum isopropoxide, isopropanol, sodium hydroxide, citric acid and water are put into a hydrothermal reactor in a mass ratio of 40:5:5:2:10:38 (the total volume of aluminum hydroxide, aluminum isopropoxide, isopropanol, sodium hydroxide, citric acid and water accounts for 70% of the hydrothermal reactor), the temperature is increased to 70°C at a heating rate of 3°C / min, the reaction is carried out at a stirring speed of 20 Hz for 3 h, and then the temperature is increased to 220°C at a heating rate of 3°C / min for 6 h to obtain an intermediate product Al2O3·nH2O, where n is 0.7.

[0118] S2: After washing, filtering, demagnetizing and drying the intermediate product, the temperature is increased to 1100° C. at a heating rate of 5° C. / min and calcined for 2 h to obtain porous alumina.

[0119] Example 7

[0120] The difference between this embodiment and embodiment 4 is that only sodium hydroxide is used as the nucleation accelerator.

[0121] Example 8

[0122] The difference between this embodiment and embodiment 4 is that only citric acid is used as the nucleation accelerator.

[0123] Comparative Example 1

[0124] The difference between this comparative example and Example 4 is that the calcination temperature is 1200°C.

[0125] Comparative Example 2

[0126] The difference between this comparative example and Example 4 is that the calcination temperature is 350°C.

[0127] Comparative Example 3

[0128] The difference between this comparative example and Example 4 is that the calcination time is 1 h.

[0129] Comparative Example 4

[0130] The difference between this comparative example and Example 4 is that the calcination time is 15 h.

[0131] Comparative Example 5

[0132] The difference between this comparative example and Example 4 is that the heating rate during the calcination process is 5.5° C. / min.

[0133] Comparative Example 6

[0134] The difference between this comparative example and Example 4 is that in S1, the temperature for hydrolysis of aluminum isopropoxide is 100°C.

[0135] Comparative Example 7

[0136] The difference between this comparative example and Example 4 is that in S1, the time for hydrolysis of aluminum isopropoxide is 12 h.

[0137] Comparative Example 8

[0138] The difference between this comparative example and Example 4 is that in S1, the temperature at which aluminum hydroxide gradually grows on the seed crystal is 100°C.

[0139] Test example

[0140] (1) Taking Example 4 as an example, the porous alumina prepared in this example was observed by field emission scanning electron microscopy and transmission electron microscopy. The results are as follows: Figures 1 to 3 As shown, Figure 1 This is the field emission scanning electron microscopy result diagram. Figure 2 and Figure 3 The transmission electron microscopy results are shown in Figure 1. Figure 3 for Figure 2 A partial enlarged view of .

[0141] Depend on Figures 1 to 3 It can be seen that the porous alumina obtained in this embodiment has an obvious pore structure, which may be due to the combined effect of the vacancies left by the removal of crystal water and the lattice rearrangement formed by the movement of aluminum ions, which ultimately form pores of different ranges.

[0142] (2) The porous alumina obtained in each embodiment and comparative example was tested for performance, and the testing method was as follows:

[0143] ①. The specific surface area is measured by using a Microsurface Analyzer in accordance with GB / T 6609.35-2023;

[0144] ② The pore size is measured by using a microsurface analyzer in accordance with GB / T 6609.35-2023.

[0145] ③. The particle size is measured by GB / T 19077-2016, laser particle size analyzer, Mastersizer 3000;

[0146] ④. The pore volume is measured by using a Microsurface Analyzer according to GB / T 6609.35-2023;

[0147] ⑤, pH is measured by acidometer according to GB / T9724-2007;

[0148] ⑥The crystal system is obtained by X-ray diffractometer;

[0149] ⑦. The morphology was observed by field emission scanning electron microscopy;

[0150] ⑧. Apparent density is tested by pycnometer method:

[0151] (a) Weigh the mass M0 of the empty bottle (in g);

[0152] (b) Fill the empty bottle with ethanol, weigh the mass M3 (in g) of the empty bottle + ethanol, then drain the ethanol and dry the empty bottle;

[0153] (c) Add a certain amount of powder into an empty bottle and weigh the mass M1 (in g) of the empty bottle + powder;

[0154] (d) Fill the bottle with ethanol and weigh the total mass M2 (in g) of the empty bottle + powder + ethanol;

[0155] The density of the powder was calculated by at least 3 measurements and the average value was taken as the apparent density of the powder.

[0156] according to Just calculate.

[0157] ⑨. The bulk density is tested using the GB / T 6609.25-2023 method.

[0158] ⑩. The surface hydroxyl content is tested using the titration method according to T / FSI 049-2020.

[0159] The performance test results are shown in Table 1 and Table 2.

[0160] Table 1 Performance test results

[0161]

[0162]

[0163] Table 2 Performance test results

[0164]

[0165] (3) Taking the porous alumina with a median particle size of 0.43 μm (denoted as AT0P50) provided in this scheme as an example, it and the commercially available conventional alumina with a particle size of 0.44 μm (as a control group, denoted as Al2O3) were prepared into diaphragms respectively, and then the liquid absorption speed and liquid absorption rate of each diaphragm were tested.

[0166] ①. The preparation method of the diaphragm is as follows:

[0167] (a) Weigh 100 g of alumina powder, add 150 ml of pure water and 1.74 g of dispersant (sodium polyacrylate with a solid content of 46%) into a high-speed disperser, adjust the speed to 1500 rpm, and disperse for 30 minutes.

[0168] (b) Reduce the rotation speed to 400 rpm, add 17.39 g of binder (acrylic resin with a solid content of 46%), 30 g of thickener (sodium hydroxymethyl cellulose with a solid content of 2%), and 0.8 g of wetting agent (polyether organosilane copolymer with a solid content of 100%) in sequence every 15 minutes, and disperse for 30 minutes to obtain a diaphragm slurry.

[0169] (c) The diaphragm is coated on a coating machine according to the required thickness (2.0 μm). The base film is selected to be a PE film. The diaphragm is dried in the shade and cut into the required size.

[0170] ②、The test method of the liquid absorption speed of the diaphragm is as follows: hang the diaphragm vertically above the electrolyte (part of it is immersed in the electrolyte, and the immersion height is consistent), and after the same time, observe the height of the electrolyte rising. The results are as follows: Figure 4 and Figure 5 shown.

[0171] Figure 4 The result after 10 minutes. Figure 5 The results are after 30 minutes.

[0172] Depend on Figure 4 and Figure 5 It can be seen that the diaphragm prepared by the porous alumina provided by the present invention can have a faster liquid absorption speed than the diaphragm prepared by conventional alumina.

[0173] ③、The test method of diaphragm liquid absorption rate is as follows:

[0174] (a) Cut the coated membrane to be tested into several 50 mm × 50 mm squares, obtain the mass of each square membrane, and take the average value as m1;

[0175] (b) The above-mentioned diaphragm is completely immersed in the electrolyte, and left for a period of time to ensure that the electrolyte is completely absorbed, and then the coated diaphragm is dried in the shade for 24 hours; the diaphragm after drying in the shade is weighed to obtain the mass of each square diaphragm after infiltration, and the average value is recorded as m2;

[0176] The calculation is based on the liquid absorption rate of the membrane = (m2-m1) / m1×100%, and the result is taken as the final liquid absorption rate of the coated membrane.

[0177] The above steps were repeated twice, that is, the test was performed in parallel twice, and the results are shown in Table 3.

[0178] Table 3 Test results

[0179]

[0180] It can be seen from Table 3 that the porous alumina provided by the present invention can enable the diaphragm to have a higher liquid absorption rate than conventional alumina.

[0181] In addition, the porous alumina obtained in each embodiment of the present invention and each comparative example was prepared into a diaphragm according to the same method as above and the liquid absorption rate of the diaphragm was tested. The results are shown in Tables 4 and 5, which show the average value of the liquid absorption rate of the diaphragm obtained from two parallel tests.

[0182] Table 4 Test results

[0183]

[0184] Table 5 Test results

[0185]

[0186] It can be seen from Table 4 and Table 5 that the diaphragm prepared with the porous alumina provided in the embodiment of the present invention can have a higher liquid absorption rate than the diaphragm prepared in the corresponding example.

[0187] In summary, the porous alumina provided by the present invention can meet the requirements of lightweight diaphragm and absorption and storage of more electrolyte, and the corresponding diaphragm can improve the electrochemical performance of lithium batteries.

[0188] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A porous alumina, characterized in that: The porous alumina has a pore structure, and the specific surface area of ​​the porous alumina is 10m 2 / g~50m 2 / g, the apparent density is 2g / cm 3 ~3g / cm 3 .

2. The porous alumina according to claim 1, characterized in that The porous alumina also has at least one of the following characteristics: Feature 1: The pore size of the porous alumina ranges from 4 nm to 80 nm; Feature 2: The particle size of the porous alumina is in the range of 0.3 μm to 2 μm; Feature 3: The pore volume of the porous alumina is 0.004 cm 3 / g to 0.08cm 3 / g; Feature 4: The pH value of the porous alumina is 8.5 to 10; Feature 5: The surface hydroxyl content of the porous alumina is >0 and ≤10 / nm 2 ; Feature 6: The porous alumina has a prismatic morphology; Feature 7: The ratio of the bulk density to the apparent density of the porous alumina is 1:9 to 2:11; Preferably, the specific surface area of ​​the porous alumina is 12 m 2 / g~50m 2 / g; Preferably, the apparent density of the porous alumina is 2.1 g / cm 3 ~2.9g / cm 3 ; Preferably, the pore size of the porous alumina is in the range of 4.0 nm to 28 nm; Preferably, the median particle size of the porous alumina is 0.4 μm to 0.5 μm.

3. The porous alumina according to claim 1 or 2, characterized in that: The pore structure includes openings and / or depressions on the surface of the aluminum oxide powder, and tunnels inside the aluminum oxide powder; The tunnels may exist in the form of independent single tunnels and / or interconnected tunnels; The hole shape of the hole structure includes circular and / or polygonal.

4. The porous alumina according to claim 3, characterized in that: Each surface of the porous alumina has at least one of openings, recesses and tunnels; When the porous alumina has tunnels, at least part of the tunnels extending inward from the surface of the alumina powder can be observed in an image with a transmission electron microscope scale of 10 nm to 50 nm.

5. A method for preparing porous alumina according to any one of claims 1 to 4, characterized in that: The following steps are involved: Aluminum hydroxide, aluminum isopropoxide, isopropanol, a nucleation promoter and water are mixed in a mass ratio of (20-40):(5-15):(5-15):(5-12):(25-58) and reacted to obtain an intermediate product Al2O3·nH2O, wherein 0.7≤n≤1.5; and the intermediate product is calcined; Preferably, the nucleation promoter includes at least one of sodium hydroxide and citric acid; More preferably, when the nucleation promoter includes sodium hydroxide and citric acid at the same time, the mass ratio of sodium hydroxide to citric acid is (1-10):5; Preferably, the total volume of the aluminum hydroxide, aluminum isopropoxide, isopropanol, nucleation promoter and water accounts for 20% to 70% of the volume of the reaction container.

6. The preparation method according to claim 5, characterized in that: The reaction comprises: first reacting at 40°C to 70°C for 3h to 5h, and then reacting at 120°C to 220°C for 6h to 24h.

7. The preparation method according to claim 5, characterized in that: The heating rate during the reaction is 1°C / min to 5°C / min.

8. The preparation method according to claim 5, characterized in that: Calcination has at least one of the following characteristics: Feature 8: Calcination temperature is 400℃~1100℃; Feature 9: Calcination time is 2h to 12h; Feature 10: The heating rate of the calcination process is 1°C / min to 5°C / min.

9. A diaphragm, characterized in that: The surface of the diaphragm is coated with the porous alumina according to any one of claims 1 to 4; Preferably, the liquid absorption rate of the diaphragm is not less than 85%.

10. A lithium battery, characterized in that: The lithium battery comprises the separator according to claim 9.

Citation Information

Cited By

  • Porous aluminum oxide for battery electrode, battery electrode, battery and electric equipment

    CN120717494A